Determining optimum rate of boron application for higher yield of wheat in Old Brahmaputra Floodplain soil (Journal of the Bangladesh Agricultural University, 2012)
The effect of different rates of boron application on wheat cv. Bijoy was studied through a field experiment at    Bangladesh Agricultural University (BAU) farm, Mymensingh during 2009-10 rabi season. The BAU farm belongs to    Old Brahmaputra Floodplain agroecological zone (AEZ 9). Texturally the soil was silt loam, with 7.2 pH, 0.81%    organic matter and 0.15 mg kg-1 available boron content. The experiment was laid out in a randomized complete    block design with five boron rates and four replications. Boron rates were 0, 0.75, 1.5, 2.25 and 3.0 kg ha-1, with boric    acid as a source. Every plot received blanket doses of 115 kg N, 25 kg P, 75 kg K and 15 kg S ha-1 from urea, TSP,    MoP and gypsum, respectively. Treatment receiving B @ 2.25 kg ha-1 produced the highest grain yield (4.22 t ha-1) which was statistically identical with that obtained with 1.75 kg B ha-1. However, the crop response curve showed    1.90 kg ha-1 to be the optimum boron rate for the maximization of wheat yield. The lowest grain yield (2.84 t/ha) was    recorded with control treatment. There was a positive relationship between grain yield and number of grains spike-1.   Boron had significant influence on N, P, K, S and B uptake by the crop which, in deed, was more influenced by crop    yield and less by nutrient concentration, except N and B uptake where concentration had more influence than yield.   DOI: http://dx.doi.org/10.3329/jbau.v9i2.10987   J. Bangladesh Agril. Univ. 9(2): 205210, 2011